Pengaruh Edukasi Kesehatan mengenai Penyakit Hipertensi pada Lanjut Usia di Panti Sosial Tresna Werdha Minaula, Kabupaten Konawe Selatan - Dian Yuniar Syanti Rahayu; Reni Devianti Usman; Nirwana Nirwana; Firnawati Firnawati (Poltekkes Kemenkes Kendari, 2018)
Hypertension is a health problem in the elderly group. As a result of rapid development and a prosperous living standards, better life expectancy, so that the numbers of elderly increasing every year. This followed with the risks of degenerative diseases and other health problems on this group. This was a quasi-experimental research with applicating hypertension health education to determine the effect to the knowledge of the elderly that living in the Panti Sosial Tresna Werdha Minaula, Kabupaten Konawe Selatan. The population of this study were all of the elderly who live in the panti, and as totally 57 elderly suffering from hypertension taken as partisipants use total sampling methode. The results showed that the differences of knowledge charateristics before and after hypertension health education regarding on knowledge of the elderly. The nurses have to continue the health education for the elderly to be better understanding about hypertension.